Aetiology of denture stomatitis - (:unkn) unknown (My University, 1993)
The purpose of this study was to determine the etiologic factors of denture stomatitis. Fifteen subjects with clinical evidence of localized simple denture stomatitis, fifteen subjects without clinical signs of denture stomatitis, and forty-five subjects with clinical evidence of generalized simple denture stomatitis were investigated clinically and mycologically. Subjects were evaluated according to age, sex, duration of denture usage, smoking habits, frequency of denture brushing, overnight denture wearing, pH level of saliva and degree of candidal colonization and candidal formation. Salivary samples and swabs were taken from the palate and the mucosal surfaces of the dentures investigated mycologically in order to identify the yeast colonies. Smears were taken from the palate and investigated in order to identify candidal formation. No statistically significant relationship was found between denture stomatitis and age, sex, duration of denture usage, frequency of denture brushing, overnight denture wearing or pH level of saliva. There was however, a statistically significant relationship between denture stomatitis and denture hygiene, smoking habits, candidal colonization and candidal formation.
Keywords: Adult; Female; Humans; Middle Aged; Turkey; Prevalence; Male; Oral Hygiene; Age Distribution; Denture, Complete; Hydrogen-Ion Concentration; Saliva; Sex Distribution; Stomatitis, Denture; Yeasts